Ailesel hipobetalipoproteinemi - (:unkn) unknown (My University, 2007)
0

In this report, we presented a case with familial hypobetalipoproteinemia (FHBL). A 34-year-old man was admitted to our hospital because of upper abdominal pain. The patient have plasma total and LDL cholesterol levels that are below half of normal and elevated plasma transaminase levels. Liver biopsy revealed steatohepatitis. In conclusion, FHBL should always be kept in mind for the etiology of fatty liver in patients with low total and LDL cholesterol levels
Familial hypobetalipoproteinemia
Keywords: Genel ve Dahili Tıp